Traveler’s Blog of Count Louis de Turenne, or Experience Economy in 1876 - E. F. Ovcharenko (Концепт: философия, религия, культура, 2025)
The relevance of the study is due to the need to investigate the cultural phenomenon of traveling and related travel journals. The rapid development of this genre along multiple trajectories (primarily travelogue as travel journalism and travel blogging) at the end of the 20th century replaced the more familiar genres of literary travel, travel essay, travel note, etc. Associated with the development of new media, travel blogs today represent a wide range of interactions, including the use of electronic means of communication. At the same time, the reference in this article to a littlestudied documentary source from the 19th century, the travel diary of Count Louis de Turenne about his journey to Quebec (winter–spring 1876), published in Paris in 1879, allows us to draw certain parallels between the travel journals of the late 1870s and the modern genre of travel blogging. The purpose of this study was determined by the discovered property of the French traveller’s journal, consisting in the desire to transmit his personalized experience in printed form in order to share impressions. Thus, this study attempts to trace parallels between the contemporary socio-cultural practice of travel blogging and its earlier prototypes. Achieving this goal required solving the following tasks: 1) to systematize the main approaches to the travel blog genre from the standpoint of cultural studies; 2) to establish the historical circumstances of the creation of the travel diary of Count Louis de Turenne; 3) to describe the personal characteristics of the Count that influenced the route he chose; 4) to trace the specifics of the phenomena that attracted his attention; 5) to correlate the cultural content of a 19th-century travel diary with the basic provisions of the latest leisure concept of the experience economy. The study is based on a comprehensive cultural analysis, which made it possible to combine the biographical method with a historical-genetic approach as well as both hermeneutic and anthropological examination of the available material. This view allowed for the tracing of the relationship between the realities of the journey, the author’s personality and the text he created (such a relationship is one of the main criteria of a travel blog, as it is commonly understood today). The material for the study was the aforementioned travel journal of Count Louis de Turenne Fourteen Months in North America (Turenne de Louis. Quatorze mois dans l’Amérique du Nord), which had not been studied by Russian scientists before. As a result, the study proposes a model for interpreting a modern travel blog as a consequence of the development of one of the directions of the travel genre, carried out in pursuit of impressions and recorded in regular diary entries. In conclusion a modern travel blog is a heterogeneous phenomenon, its comprehensive consideration in the optics of cultural studies can help to identify a number of non-trivial features. The historical circumstances of the creation of the studied journal do not allow us to fully project ideas about modern travel blogs onto this work. At the same time, an analysis of the diary’s content revealed a number of their typological similarities, the main one of which is the attitude to impressions as a value. Thus, the diary of Louis de Turenne can be considered a prototype of both modern travel blogging and a proto-phenomenon of the experience economy.